2014
DOI: 10.1111/1469-0691.12608
|View full text |Cite
|
Sign up to set email alerts
|

Sequential time to positivity of blood cultures can be a predictor of prognosis of patients with persistent Staphylococcus aureus bacteraemia

Abstract: A short time to positivity (TTP) correlates with poor clinical outcome in patients with Staphylococcus aureus bacteraemia, but the association between sequential TTPs and the outcome of these patients is unclear. Sequential TTPs from patients with S. aureus bacteraemia persisting for >48 h were analysed with respect to clinical parameters and patient outcome at a tertiary hospital. During the 5-year study period, 87 patients (9.2%; mean age of 64 years) had persistent S. aureus bacteraemia, with an average Pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
(42 reference statements)
0
14
0
1
Order By: Relevance
“…Previous studies have shown that a short time to positivity is associated to poor clinical outcome in S. aureus bacteraemia [31,32]. It has also been suggested that in patients with persistent S. aureus bacteraemia a sustained short time to positivity in the follow-up blood culture can be a marker for mortality risk [33,34]. In addition, persistence of bacterial DNA in blood (using the multiplex PCR-test SeptiFast) has been associated to endovascular complications in S. aureus bacteraemia [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a short time to positivity is associated to poor clinical outcome in S. aureus bacteraemia [31,32]. It has also been suggested that in patients with persistent S. aureus bacteraemia a sustained short time to positivity in the follow-up blood culture can be a marker for mortality risk [33,34]. In addition, persistence of bacterial DNA in blood (using the multiplex PCR-test SeptiFast) has been associated to endovascular complications in S. aureus bacteraemia [35].…”
Section: Discussionmentioning
confidence: 99%
“…This important exception reflects that TTP from S. aureus bacteraemia is complex and presents atypical characteristics. Fourth, TTP is probably useful in monitoring patients treated for S. aureus bacteraemia, as failure to increase TTP by at least 50% in sequential blood culture was more frequently associated with a new focus on infection and death [15], suggesting that more aggressive treatment should be prompted with such TTPs. Fifth, TTP was advocated for distinguishing between methicillin-resistant and methicillin-susceptible S. aureus, but the literature presents conflicting data [7,10].…”
mentioning
confidence: 99%
“…Disseminated infection foci can be difficult to identify and failure to eradicate them is associated with persistent bacteremia and poor outcomes [3,4]. In turn, the likelihood of dissemination is related to the duration of bacteremia, underscoring the importance of the rapid application of appropriate therapeutics [1,3,5]. Unsurprisingly, antibiotic resistance poses a significant therapeutic challenge and bacteremia caused by methicillin-resistant S. aureus (MRSA) is strongly associated with persistent bacteremia and carries a higher mortality rate than that caused by sensitive isolates [3,4,6].…”
mentioning
confidence: 99%